Remaja Dan Kafe Teenagers And Cafes - Firdaus W Suhaeb (Universitas Negeri Makassar, 2023)
Abstract: This research article aims to know and describe the motivations and social actions of adolescent adolescent café visitors in Barru City. Research informants were selected by purposive sampling, with the criteria, aged 17 – 21 years, unmarried, and every week being a café visitor. This research is a descriptive research with a qualitative approach. Data collection is carried out through observation, documentation, and in-depth interviews then the data obtained is analyzed using descriptive methods with stages of data reduction, data display, and conclusion. Data validation techniques are used by member checks. The results showed that there are different motivations behind teenagers to visit cafes, namely (1) intrinsic motivation, such as feeling pleasure, comfort, pride and satisfaction, (2) extrinsic motivation, such as getting rewards in the form of praise. Then the type of action from teenagers to visit a café, namely (1) the existence of instrumental rational actions, such as they visit a café as a place to meet primary needs, namely eating and drinking, hanging out, refreshing ̧ relieve fatigue, follow trends, interact with others, get new acquaintances, and as a place to use Wi-fi. (2) the existence of value-oriented actions, such as self-actualization events to show existence. (3) affective actions, such as feeling happy, and feeling satisfaction when in a café.